Answer Sheet
Answer Sheet
Answer Sheet
f (2 − 1) = f (1) = 1 + 3 = 4
√
(3) 3 33 (units) ID: [0B253]
9 12
6
C x D 2x B
w + .25l = 2500
w + .75l = 3700
Subtracting the first equation from the second gives .5l = 1200 ⇒ l = 2400. Substituting this back into the
first equation give w + .25(2400) = 2500 ⇒ w = 1900 .
441b = 4b2 + 4b + 1 = n2
351b = 3b2 + 5b + 1 = (n − 2)2
We substitute the area of the rectangle, A = xy, to get d2 = 100 − 2A. Solving for A in terms of d2 gives
1
A = 50 − d2 .
2
A
C
Similarly, there are 3 paths of A to each midway point. Furthermore, there are 3 paths from each midway
point to B.
So for each unique path, we pick from 6 midway points, pick from 3 paths from A to the midway point, and
pick from 3 paths from the midway point to B. This gives 6 × 3 × 3 = 54 short paths.
A = (3, 4)
r O
B
yz = 2
y · 3y = 2
2
y2 = .
3
2
1 3 2
Then, we have x2 = y = 2 and z 2 = (3y)2 = 9y 2 = 9 · 3 = 6. Therefore, the value of x2 + y 2 + z 2 is
3 2 9 4 36 49
2 + 3 +6= 6 + 6 + 6 = .
6
A B
D M C
Since CT and BM are medians of △BCD, point O is the centroid of △BCD, so OC = (2/3)CT . Since T is
the midpoint of AC, we have CT = AC/2, so OC = (2/3)CT = (2/3)(AC/2) = AC/3. Since OC is 13 of AC,
2
we know that OA is the other 3 of AC, which means OC/OA = 1/2 .
abc = 12,
and
4(a + b + c) = 28.
These equations can be simplified: ab + bc + ca = 16, abc = 12, a + b + c = 7.
We want to find (a + 1)(b + 1)(c + 1), which we expand as follows:
We conveniently have the values of the expressions in parentheses from our earlier equations, so we substitute:
For 6 + p to be positive, p must be 3, so the first three terms of the sequence are 3, 6 + 3 = 9, and 30 − 3 = 27.
Thus, we have a geometric sequence with first term 3 and common ratio 3. Therefore, the fifth term of this
sequence is 3 · 34 = 243 .
A G E
2
D
2
B 2 C F
O Q
P
B D C
O
P
Let O be the center of the sphere (or the center of the circle in the cross-section), let the triangle be △ABC,
so that D is the midpoint of BC and A is the apex (as △ABC is isosceles, then AD is an altitude). Let P be
the point of tangency of the circle with AC, so that OP ⊥ AC. It follows that △AOP ∼ △ACD. Let r be
the radius of the circle. It follows that
OP CD
= =⇒ OP · AC = AO · CD.
AO AC
√ √
We know that CD = 12, AC = 122 + 242 = 12 5, OP = r, and AO = AD − OP = 24 − r. Thus,
√ √
12r 5 = 12(24 − r) = 122 · 2 − 12r =⇒ 12r(1 + 5) = 122 · 2.
24
Thus, r = √ .
1+ 5
Multiplying the numerator and denominator by the conjugate, we find that
√ √
24 5−1 24( 5 − 1) √
r= √ ·√ = = 6 5 − 6.
1+ 5 5−1 5−1
It follows that a + c = 11 .
1 − x = 4(1 − 2x)
1 − x = 4 − 8x
7x = 3.
6
So x = 73 . The probability that Mark sinks a free throw in 2010 is double this probability, or .
7
D F C
x
2
√ 1
x 3 x
2 2
E
x
A B